2018
DOI: 10.1038/s41598-018-25567-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for landslide displacement prediction by integrating advanced computational intelligence algorithms

Abstract: Landslide displacement prediction is considered as an essential component for developing early warning systems. The modelling of conventional forecast methods requires enormous monitoring data that limit its application. To conduct accurate displacement prediction with limited data, a novel method is proposed and applied by integrating three computational intelligence algorithms namely: the wavelet transform (WT), the artificial bees colony (ABC), and the kernel-based extreme learning machine (KELM). At first,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…It is recognized that the model having lower values of RMSE and MAE implies better prediction performance. For more information about them, see the literature [30], [31]. In this paper, we also adopt these two indicators to evaluate our model, and the RMSE and MAE can be expressed as…”
Section: B Prediction Processmentioning
confidence: 99%
“…It is recognized that the model having lower values of RMSE and MAE implies better prediction performance. For more information about them, see the literature [30], [31]. In this paper, we also adopt these two indicators to evaluate our model, and the RMSE and MAE can be expressed as…”
Section: B Prediction Processmentioning
confidence: 99%
“…However, the simulation technique is always complicated, and it requires accurate soil parameters, which are difficult to obtain. Recently, with the development of machine learning (ML) technique, numerous ML models, including hybrid, ensemble, deep learning, etc., have been widely utilized in geology and environment studies [19][20][21]. Choubin et al applied simulated annealing feature selection to identify key features, and five ML models were used to predict the earth's fissure hazard [22].…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring and early warning (EW) systems for the detection of natural hazards are usually based on a network of sensors and related to developments in geospatial engineering (Bhattacharya et al, 2012), which enable the protection of infrastructure and populations, and the mitigation of long-term consequences (Kubo et al, 2011). The developments of GPS technology, that is, sampling rate up to 100 Hz (HĂ€berling et al, 2015;Zhou et al, 2018), the introduction of additional satellite systems as GLONASS, BeiDou, Galileo, and so forth (Msaewe et al, 2017;Teunissen et al, 2014), and the broad operation of permanent GNSS networks (Bock & Melgar, 2016) provide continuous time series of GNSS products, which can reflect potential ground deformation (Liu et al, 2017;Reilinger et al, 2006) and troposphere/ionosphere abnormalities (Wielgosz et al, 2005), all of which are related to geohazards. More specifically, GNSS coordinate time series are used in applications for the estimation of earthquake magnitude (Blewitt et al, 2006;Wright et al, 2012) and earthquake characteristics (Geng et al, 2013;Melgar et al, 2013;Psimoulis et al, 2014), tsunamis (Ohta et al, 2012), hydrological loadings (van Dam et al, 2001;Tregoning et al, 2009), vertical land movements and sea-level rise (Teferle et al, 2006), and ionospheric storms (Wielgosz et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…), and the seismic wave detection (PĂ©rez-Campos et al, 2013) or to predict the generation of tsunamis (Blewitt et al, 2009). A similar approach is also followed for the application of GNSS networks in the monitoring of landslides and the modeling of ground motion (Benoit et al, 2015;Zhou et al, 2018). Furthermore, recent studies have revealed the potential contribution of high-rate GNSS data in earthquake early warning systems by estimating the predominant period (Psimoulis, HouliĂ©, & Behr, 2018) and the peak displacement (Crowell et al, 2016) of the P-waves, supplementing the current seismic data-based early warning techniques.…”
Section: Introductionmentioning
confidence: 99%